2014
DOI: 10.3846/16486897.2014.931283
|View full text |Cite
|
Sign up to set email alerts
|

Air Stream Velocity Modelling in Multichannel Spiral Cyclone Separator

Abstract: Trinitrotoluene (TNT), a commonly used explosive for military and industrial applications, can cause serious environmental pollution. 28-day laboratory pot experiment was carried out applying bioaugmentation using laboratory selected bacterial strains as inoculum, biostimulation with molasses and cabbage leaf extract, and phytoremediation using rye and blue fenugreek to study the effect of these treatments on TNT removal and changes in soil microbial community responsible for contaminant degradation. Chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…For example, at the gas flowrate of 113 m -3 h corresponding to the velocity of 16 m s -1 , the cyclone pressure drop was measured as 1200 Pa [35]. On the other hand, a spiral cyclone-separator induces higher pressure drops due to a larger radius of curvature, and therefore the gas velocity should be up to 15.4 m s -1 [36]. Next, the aerodynamic resistance was analyzed in the multi-channel cyclone under a 50/50 flow distribution ratio between the transitional and peripheral flows using quarter-rings with a 5° opening angle of plates.…”
Section: Resultsmentioning
confidence: 99%
“…For example, at the gas flowrate of 113 m -3 h corresponding to the velocity of 16 m s -1 , the cyclone pressure drop was measured as 1200 Pa [35]. On the other hand, a spiral cyclone-separator induces higher pressure drops due to a larger radius of curvature, and therefore the gas velocity should be up to 15.4 m s -1 [36]. Next, the aerodynamic resistance was analyzed in the multi-channel cyclone under a 50/50 flow distribution ratio between the transitional and peripheral flows using quarter-rings with a 5° opening angle of plates.…”
Section: Resultsmentioning
confidence: 99%
“…In order to estimate the d 50 value at a certain temperature, it is of uttermost importance to determine the empirical correlation between d 50 and air temperature. The correlation between d 50 and air temperature when capturing particulate matter at temperatures in the interval of 20-120 • C can be described, according to the following empirical formula: y = 4.6758 e 0.0558x (9) where x-air temperature, • C; y-d 50 µm; d 50 -50% of particulate matter removal efficiency in the new design multi-channel cyclone. This empirical formula is suitable to describe the dependency of d 50 on air temperature (in the measured temperature interval) because it corresponds with a high correlation coefficient's value (R 2 = 0.891).…”
Section: Theoretical Evaluation Of Impact Of the Gas (Air) Temperatur...mentioning
confidence: 99%
“…The combination of dust-polluted flow filtering and centrifugal purification is a new direction in centrifugal purification device improvement. These new generation multi-channel cyclones have been studied by scientists in many European countries [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the efficiency of the device increases as the inlet flow gets higher. The emission problem, while using numerical modelling, was investigated in [32]. A multichannel cyclone is a new-generation cleaning device that purifies gas flow and removes dispersion solid particles of 2 µm and those larger in diameter from it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Almost no "Dormashina" machinery is left, as the units were replaced with new or shortly used AMPs, the number of which is listed in Table 2. The most popular 103 operating AMPs in the Baltic States represent "Teltomat" (32), "Benninghoven" (31), "Ammann" (13) and "Amomatic" (11) AMPs. Most AMPs operate in Lithuania (47) and the smallest number is observed in Estonia (23), which correlates with the area and population of the countries.…”
Section: The Current Situation and Scenarios For Renewing The Asphalt Mixing Plants' Fleetmentioning
confidence: 99%